Evolutionary history of microgastrine wasps (hymenoptera: braconidae: microgastrinae) in Sundaland: insights from Peninsular Malaysia - Aman-Zuki, Ameyra; Mohammed, Muhamad Azmi; Badrulisham, Aqilah Sakinah; Idris, Muhammad Ikhwan; Salbi, Mohd Fuat; Yaakop, Salmah (Springer Nature, 2025)
Microgastrinae is a subfamily of lepidopteran endoparasitoids that consume angiosperm nectar as their primary food source. Despite several studies on their biology and phylogeny, the evolutionary history of Microgastrinae remains poorly resolved. A total of 146 sequences were obtained from three markers—28S, 16S, and COI—from 55 Microgastrinae individuals collected from oil palm plantations and forests in Peninsular Malaysia. The objective of this study was to investigate the evolutionary history of this subfamily, using organisms from Peninsular Malaysia as a model. Thirteen genera were included in the analysis. The molecular clock analysis estimated that the Sundaland Microgastrinae species diverged around 51.93 million years ago (mya) in the Eocene, which is consistent with the crown age of this family. The Fornicia genus was estimated to be the earliest genus, evolving approximately 51 mya. The Apanteles group radiated from 45.83 mya. The Microplitis group diverged at 29.74 mya, while the Neoclarkinella genus evolved at 24.16 mya. The paraphyletic group of Cotesia diverged multiple times, between 32.39 and 13.88 mya. Angiosperms radiated during the Eocene to Oligocene, around 55–23 mya, while lepidopteran species evolved at the beginning of the Miocene, from 23.0 to 15.0 mya; thus, both groups overlapped with the radiation of Microgastrinae. Interestingly, the coevolution between microgastrines, angiosperms, and lepidopteran species from Sundaland was found to be congruent and supported by global data. These findings may contribute new information on the systematics, biology, and evolution of Microgastrinae by providing samples collected from Peninsular Malaysia with a particular focus on Sundaland coevolution with angiosperms and Lepidoptera.